Fecundity and condition factor of abalone Haliotis asinina broodstock conditioned in banana leaf and "buho"slat substrates - De Guzman, Argie L.; Creencia, Lota A. (2014)
This study was conducted to document the spawning behaviour and determine the fecundity and condition factor of the female abalone Haliotis asinina broodstock conditioned using two indigenous substrates, the banana (Musa spp.) leaf and “buho” (Schizostachyum lumampao)
slat, for three months at Western Philippines University-Binduyan Marine Research Station (WPU-BMRS). Those abalone conditioned with no substrate served as control. Forty-five female broodstocks with 5-7cm shell length were used in the study. The spawning episode of the three treatments did not correlate with the lunar cycle. They spawned either later or earlier than the full moon and new moon. Spawning happened 3-5 nights in a row with an interval of 8-10 days. There was no significant difference (P>0.05) among the three treatments on the number of individuals that spawned within the four spawning episodes. Abalone conditioned in banana leaf substrate had an average fecundity of 259,353.21±39,307.63 eggs. However, there was no significant difference among treatments (P>0.05). The initial and final condition factors of each treatment were significantly different (P<0.01) but there were no significant differences on the condition factor among treatments. The indigenous substrates, banana leaf and buho slat are potential alternative substrates for broodstock conditioning. However, spawning performance and fecundity of abalone broodstock were not influenced by the substrates. Similar long-term studies are recommended.
Keywords: Abalone culture; Organic substrates